Photo and thermal degradation of Glyphosate and Fluazifop-butyl herbicides with and without additives - Balah , Mohammed. A.; Gamal Aldin , Abdel-Rahman; Zidan, Zidane. H.; Dahroug, Sayed. A. (Al-Mukhtar Journal of Sciences, 2017)
The study investigated the effect of some additives on glyphosate and fluazifop-butyl herbicides light-decomposition by ultraviolet rays and temperature were studied under laboratory conditions. Based on the results, additives have a varying influence on their photo and thermal decomposition of both studied herbicides substance. Generally, additives of glue, dioleate, monoleate and mineral oil were the most effective material for lowering the rate of glyphosate degradation by UV rays. Meanwhile, the effect of paraffin oil and urea were not significant in glyphosate thermal degradation, and the dual combination of glyphosate with additives reduced degradation rate regardless of the thermal exposure especially when mixed with glue and then dioleate and monoleate. Glyphosate was more susceptible to the thermal decomposition than photolysis by UV radiation. The change in fluazifop-butyl herbicides without or with binary mixture additives amount under the studies UV radiation and temperature was very low and was stable in the studied systems. On the others side, the effect of temperature on fluazifop-butyl degradation was very low in the absent or present of additives, but using additives with the herbicide gave a relative protection to herbicides. The mixture of fluazifop-butyl with rapeseed oils or mineral oils slightly accelerate the herbicide photodecomposition curves. In conclusion,. Some additives gave a relative protection to glyphosate to face deterioration by UV radiation and temperature. Therefore, using glyphosate for weed control requires avoiding direct sunlight with the help of any of the above additives, as it should be noted not to fear from the accumulation of glyphosate residue in these agro-environment areas for the rapid deterioration and degradation.